MONITORING MANGROVE AREA IN BENOA BAY USING LANDSAT TM AND ETM + DATA - Ari Sugianthi, Ni Luh Made; Arthana, I Wayan; Sandi Adnyana, I Wayan (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2012)
Mangrove ecosystems are crucial for the management of some coastal resources in Indonesia. This research used Landsat TM 1994, Landsat ETM+ 2002 with the purpose to know mangrove area change for eight years, mangrove density and accuracy of image as source of data to mangrove area in Benoa Bay. From image analysis that using maximum likelihood method, the mangrove is classified into 3 classes i.e.: mangroves with high density, medium density and low density. For the ground check, used single plot method by using 6 trees. The extent of mangrove area in Benoa Bay were 447.69 ha in 1994 and 622.08 ha in 2002. The change of the extent of mangrove area during 8 years (1994 – 2002) increased by 174.41 ha. The area of densities in 1994, high density was 225.15 ha, medium density was 122.48 ha and low density was 130.05 ha. In 2002, high density was 262.8 ha, medium density was 265.95 ha, and low density was 133.30 ha. Based on the regression analysis between mangrove density and the value of interpretation, the density of mangrove in Benoa Bay which the criteria of high density is 364.723 – 466.311 tree/ha, medium density is 237.738 - 364.723 tree/ha and low density is 186.944 – 237.738 tree/ha. The determination coefficient (r2) was 0.6312. Based on the regression analysis in 2002 used in interpretation of mangrove density in 1994, which the criteria of high density is 357.10 tree/ha –316.47 tree/ha, medium density is 273.29 tree/ha – 316.47 tree/ha and low density is 252.98 tree/ha –273.29 tree/ha. The accuracy of the Landsat ETM+ 2002 for mangrove area classification in Benoa Bay was 90%. These values were above the acceptable limit of accuracy stated of 80 %, so that this classification accuracy was acceptable.
Keywords: monitoring, mangrove, density, sattelite data